Remaking Ukraine after World War II : the clash of local and central Soviet power - Slaveski, Filip ca. 20./21. Jh (New studies in European history, 2021)
Ukraine was liberated from German wartime occupation by 1944 but remained prisoner to its consequences for much longer. This study examines Soviet Ukraine's transition from war to 'peace' in the long aftermath of World War II. Filip Slaveski explores the challenges faced by local Soviet authorities in reconstructing central Ukraine, including feeding rapidly growing populations in post-war famine. Drawing on recently declassified Soviet sources, Filip Slaveski traces the previously unknown bitter struggle for land, food and power among collective farmers at the bottom of the Soviet social ladder, local and central authorities. He reveals how local authorities challenged central ones for these resources in pursuit of their own vision of rebuilding central Ukraine, undermining the Stalinist policies they were supposed to implement and forsaking the farmers in the process. In so doing, Slaveski demonstrates how the consequences of this battle shaped post-war reconstruction, and continue to resonate in contemporary Ukraine, especially with the ordinary people caught in the middle